A ineficácia da Lei Maria da Penha no feminicídio - COSTA, Catiely da; LOPES, Helena Garcia; IGLESSIAS, Laura Bueno; FERREIRA, Manuela Miranda; AMARAL, Marcus Vinícius Nascimento; FAUSTINO, Sophia Lopes (151, 2024)
A Lei Maria da Penha, criada em 2006, é um avanço na luta contra a violência de gênero, mas enfrenta desafios na prevenção do feminicídio. A implementação da lei é muitas vezes inadequada devido à falta de infraestrutura e capacitação nas delegacias, além da persistência de uma cultura machista. As medidas protetivas não são sempre eficazes, pois podem ser desrespeitadas, e o feminicídio não é devidamente considerado nas investigações, levando a subnotificações. Assim, é necessário um esforço maior para garantir a efetividade da lei, incluindo educação, mudanças culturais e melhorias na proteção às mulheres. ABSTRACT The Maria da Penha Law, created in 2006, represents a step forward in the fight against gender-based violence, but it faces challenges in preventing femicide. The law’s implementation is often inadequate due to a lack of infrastructure and training in police stations, in addition to the persistence of a sexist culture. Protective measures are not always effective, as they can be disregarded, and femicide is not properly considered in investigations, leading to underreporting. Thus, greater efforts are needed to ensure the law’s effectiveness, including education, cultural changes, and improvements in the protection of women.
The ineffectiveness of the Maria da Penha Law in feminicide
Keywords: Feminicídio; Lei; Gestão e Negócios